ONGONITES AND ELVANITES - Dergachev V.B. (My University, 1991)
An examination was made of the nomenclature, distribution, petrogeochemical characteristics and relationship with mineralisation of dyke rocks with an exotic rare-metal composition - ongonites (sodium branch) and elvanites (potassium branch). A description is given of their associations with geochemical types of rare-metal granites - plumasite leucogranites and granitoids belonging to the subalkaline series. New types of ultra-rare-metal and rare-metal pantellerites and comendites associated with agpite rare-metal granite are predicted.